Influence of breastfeeding on blood‐cell transcript‐based biomarkers of health in children. Issue 6 (26th November 2013) - Priego, T.; Sánchez, J.; Picó, C.; Ahrens, W.; Bammann, K.; De Henauw, S.; Fraterman, A.; Iacoviello, L.; Lissner, L.; Molnár, D.; Moreno, L. A.; Siani, A.; et al.
Summary: What is already known about this subject: The expression of specific genes in peripheral blood cells (PBCs) may be used as biomarkers of the metabolic status. High levels of expression of CPT1A, SLC27A2, INSR, LEPR, FASN and PPARα in PBCs are indicative of a lower risk for the insulin resistant or dyslipidaemic state associated with obesity in children. Breastfeeding seems to confer protective effects against obesity and its related metabolic problems. What this study adds: Children who had been breastfed showed higher expression levels of SLC27A2, FASN, PPARα and INSR in PBCs compared with formula‐fed subjects. The relationship of the PBC transcript levels of SLC27A2, INSR, FASN and PPARα with insulin resistance and dyslipidaemia may be dependent on the type of infant feeding (breast vs. formula). The transcript levels of the mentioned biomarkers could be useful to distinguish the formula‐fed children who are at higher risk of metabolic alterations. Background: Blood‐cell transcripts have showed to be good biomarkers of metabolic alterations and their use in early detection and prevention of future disorders is promising. Objective: This study aimed to examine the relation between previously proposed transcriptional biomarkers of metabolic health ( SLC27A2, CPT1A, FASN, PPARα, INSR, LEPR ) in peripheral blood cells and the type of infant feeding in a subset of children from the IDEFICS (Identification and Prevention of Dietary‐ and Lifestyle‐Induced Health Effects in Children and Infants) cohort. Subjects: A total of 237 children aged 2–9 years from eight European countries were studied. Results: Breastfed children showed higher expression levels of SLC27A2, FASN, PPARα and INSR, and lower risk of being overweight and of having high plasma triglyceride levels vs. formula‐fed children. Besides, overweight formula‐fed children presented higher HOMA‐index than overweight breastfed children (1.90 vs. 1.62); however, this negative effect was absent in formula‐fed children with high expression of SLC27A2 . Moreover, formula‐fed children with low expression of SLC27A2, FASN, PPARα and INSR presented higher triglyceride levels than subjects with high expression of these genes (77.7 mg dL −1 vs. 44.8 mg dL −1 ). This difference was absent in breastfed children. Conclusions: Protective effects of breastfeeding are reflected in higher expression levels of SLC27A2, FASN, PPARα and INSR in blood cells. These biomarkers may also serve to discriminate the formula‐fed children that are at higher risk of metabolic alterations.